Pengaruh Penerapan Sistem Control Valve Cooler 1 Berbasis Microcontroller ATmega 2560 Terhadap Moisture Pakan After Mixing dengan Bagging Off di PT. Japfa Comfeed Indonesia, Tbk. Unit Padang - Eko Solihin; Sukardi Sukardi (JTEV (Jurnal Teknik Elektro dan Vokasional), 2020)
This research aims to know and analyze the effect of application of control valve Cooler 1 Based On atmega 2560 microcontroller for Moisture feed after mixing with bagging off at PT. JAPFA comfeed Indonesia, Tbk. Unit Padang. The type of research used is the study of surveys with the analysis of data used i.e. simple linear regression analysis. Based on the results of the study, testing of normality obtained the significance value of 0.200 with normal categories and R square test results worth 29.4%. The results of simple linear regression test partially with T test, Mempertlihatkan that the application of the control valve Cooler 1-Base atmega 2560 microcontroller system significantly affects the after-mixing Moisture feed with bagging off. The interpretation is that each temperature reduction of the resulting control valve cooler 1 Microcontroller-Based atmega 2560 in one unit affects the difference of moisture feed after mixing with a bagging off of 2.425.